Reparations as a Public Health Priority — A Strategy for Ending Black–White Health Disparities - Bassett, Mary T; Galea, Sandro (The New England journal of medicine, 2020)
The Black–White health gap is inseparable from the enormous gap in resources between U.S. Blacks and Whites. The radical implication of this link is that what really needs fixing is access to resources. One means for fixing it is Black reparations for slavery.